PERAN ORANG TUA DALAM MENGATASI KENAKALAN REMAJA STUDI KASUS DI KELURAHAN LETTE KECAMATAN MARISO KOTA MAKASSAR - Soekarno; Bahtiar, Abd. Rahman; Ridha, Abdul Azis (LPPM Universitas Islam 45, 2024)
The purpose of this study was to determine the role of parents in providing guidance on efforts to overcome juvenile delinquency in Lette Village, Makassar City. The research method uses qualitative with data collection techniques used, namely observation, interviews, and documentation. After that the collected data is analyzed with the stages of data reduction, data presentation and verification or drawing conclusions. The results of this study show that the problems studied are related to the role of parents in overcoming juvenile delinquency. It was found that the role of parents in overcoming juvenile delinquency includes participating in youth religious activities in Lette Village, sports lessons to avoid juvenile delinquency activities at night. The main supporting factors are good communication between parents and children, a harmonious and stable family environment. Various obstacles often hinder the role of parents in overcoming juvenile delinquency in this area. One of the main inhibiting factors is the lack of time between parents and children, the factor of peers who behave badly, the surrounding environment is not good, and the factor of people who have low human resources.